The Cost of Graduation and Academic Rituals: Material Expressions of Student Life in the Late Middle Ages in Portugal - Norte,Armando (2019)
Medieval universities were always institutions where certain rituals were regularly performed in varying forms and at different places and moments. Such practices have also been identified as taking place at the Portuguese University, where they marked important moments in a student's life, involving, for example, processions or graduation ceremonies. These were solemn events displaying a strong urban identity, which followed routes that passed by important and symbolic places in the city (cathedrals, churches, public squares, etc.), often complemented by the celebration of religious masses and sermons. The aim of this paper is to reconstruct the urban itineraries followed by the members of universities and the costs and revenues involved in these acts, as expressed in the university statutes issued by King Manuel I (c. 1503).